A Brief Review of Firefly Algorithm: Application in Structural Optimization Problem - Tripathi, Sujan (Journal of the Institute of Engineering, 2019)
Firefly Algorithm is a recently developed meta-heuristic algorithm, which is inspired by the flashing behaviour of Firefly. Initially, Firefly algorithm was used to solve the optimization problems of continuous search domain. Further, many researchers have successfully implemented this algorithm in several discrete optimization problems. Although the firefly algorithm behaves like another meta-heuristic method (i.e. Particle Swarm Optimization particle), however, the firefly is robust than that. Due to the presence of an exponential term in its movement equation, firefly algorithm is capable to search optimum value more efficiently than others. This study is, mainly, focused to show the strength of the firefly algorithm to solve the complex problems and to explore the possible research area on the structural engineering field. This study shows about the robustness of the firefly algorithm on the basis of recently published papers that was used to solve the size, shape and topology optimization of the spatial truss structure with discrete design variables. The review result shows that the performance of the Firefly Algorithm is remarkable compared to other nature-inspired-algorithms, such as particle swarm optimization. This study concludes with some remarkable points that will be more beneficial to the future researchers of this area.